Development of encyclopedia in biology “Growth and Development” enriched with an information of stunting - Pasaribu, Erna Cristina; Candramila, Wolly; Mardiyyaningsih, Asriah Nurdini (Jurnal Mangifera Edu, 2024)
Print media such as encyclopedia still holds advantages in learning. As learning media, encyclopedias can be employed to convey current issues occurring in society that are broad and highly important. The high prevalence of toddlers with stunting indicates is crucial to be presented comprehensively. Encyclopedia can act as enrichment by discussing material that can broaden students' perspectives and understanding. However, limited encyclopedias have been developed. This research aims to develop an encyclopedia as a learning medium for Growth and Development material in high school. Enrichment with stunting information is aimed not only at increasing students' understanding, but also at supporting government programs related to efforts to reduce national stunting rates. The research and development method applied uses the ADDIE model which is limited to the first three stages (analysis, design, and development). The initial product is tested for suitability in six aspects, namely presentation, graphics, layout, content, language and use by 5 validators. The validity calculation uses the Aiken's V formula and the final value is 0.93. Referring to the minimum validity value for five validators, the encyclopedia that has been developed meets the valid category in all aspects and indicators. It is hoped that further research can be carried out to implement encyclopedias in learning.